Smart Fish Feeder Dengan Medeteksi Jumlah Getaran Permukaan Air Kolam Berdasarkan Tingkat Kelaparan Ikan - Jatmiko Endro Suseno; Agus Setyawan; Thessa Putri Aulia (Jurnal Penelitian Pendidikan IPA, 2025)
Suboptimal fish feeding management can affect the growth rate of fish. Fish   Feeding management consists of aspects of feed nutritional content, quantity, and feeding system. A system that still relies on humans or manual labor is very likely to cause human error in the process, so utilizing technology can be an option to improve the feeding system. This study aims to design and test the Smart Fish Feeder Design as an innovation in technology-based freshwater fish feeding. The fish Feeder works by providing fish feeding scheduling using the RTC DS3231 and detecting vibrations in pond water, which aims to determine the feeding process using the SW-420 Vibration Sensor. If a certain vibration is used as a parameter that the fish are still consuming feed, then the feeding process continues. The duration of the influence of sensor readings in adding feed lasts for one minute and can be adjusted according to pond conditions or the number of research subjects. The results show that the design can provide fish feed on a scheduled basis with high accuracy and can detect water vibrations as an indicator of feed consumption by fish.